Comparative Analysis of Techniques for Solving the Hydraulics of Pressurized Irrigation Pipe Networks - Numan Mizyed (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
This study presents a comparative analysis for three techniques in analyzing the hydraulics of pressurized irrigation systems: Linear Theory, Newton Raphson, and Iterative Distal Outlet. It was found that the iterative distal outlet method uses less computer time and memory than Newton Raphson and Linear theory methods in analyzing the hydraulics of pressurized irrigation systems. The study shows that using an approximate initial solution for such systems, which can be obtained using Wu-Gitlin approach, will significantly improve the convergence rate of this iterative method as well as the other methods.